Obtaining a social assistance by children with disabilities: theoretical and legal aspect - Inshin, Nikolay (Київський національний університет імені Тараса Шевченка, 2017)
The article describes the legal regulation of social assistance to disabled children. Some problems of existing regulations are identified, the ways of their elimination and improving the procedure of providing this care are proposed.

Стаття присвячена вивченню основних засад правового регулювання надання соціальної допомоги дітям-інвалідам. Виявлено окремі недоліки чинних нормативно-правових актів, запропоновано їх усунення та вдосконалення порядку надання зазначеної допомоги.
ОТРИМАННЯ СОЦІАЛЬНОЇ ДОПОМОГИ ДІТЬМИ-ІНВАЛІДАМИ: ТЕОРЕТИКО-ПРАВОВИЙ АСПЕКТ
Keywords: children with disabilities; social assistance; legal regulation; діти-інваліди; соціальна допомога; правове регулювання